2018
DOI: 10.1063/1.5047025
|View full text |Cite
|
Sign up to set email alerts
|

Impedance spectroscopy of Bi-rich BiFeO3: Twin thermal-activations

Abstract: Transport measurements data are presented on bismuth-rich BiFeO3 ceramic, synthesized by a solid state method. Conductivity isotherms were analyzed using Jonscher’s empirical power-law frequency dependence. Monotonically increasing frequency-exponent n(T) over 413–593 K indicates a small polaron tunnelling mechanism for the charge transport. Distinct linear regimes observed in the Arrhenius σdc vs. T−1 plot suggest that two different charge-carriers/conductivity-relaxations prevail above and below ∼490 K. Twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…From Figure 8 , it can also be observed that E A,cond increases from 0.18 eV to 0.25 eV for sample S1, from 0.21 eV to 0.29 eV for sample S2 and from 0.23 eV to 0.32 eV (or sample S3, being in accordance with the values obtained by other authors [ 28 , 29 ], for similar samples. Therefore, the obtained results show that the thermal activation energy of the static conductivity of samples S2 (with Bi 2 O 3 impurities) and S3 (with Fe 2 O 3 impurities) is higher than that corresponding to the pure sample S1 (BFO), being in correlation with the σ DC values obtained for these samples (see Figure 4 ).…”
Section: Resultssupporting
confidence: 90%
“…From Figure 8 , it can also be observed that E A,cond increases from 0.18 eV to 0.25 eV for sample S1, from 0.21 eV to 0.29 eV for sample S2 and from 0.23 eV to 0.32 eV (or sample S3, being in accordance with the values obtained by other authors [ 28 , 29 ], for similar samples. Therefore, the obtained results show that the thermal activation energy of the static conductivity of samples S2 (with Bi 2 O 3 impurities) and S3 (with Fe 2 O 3 impurities) is higher than that corresponding to the pure sample S1 (BFO), being in correlation with the σ DC values obtained for these samples (see Figure 4 ).…”
Section: Resultssupporting
confidence: 90%
“…The binding energy of O-1s in the range of 530.20–532.30 eV and 533.20–534.80 eV was allocated to oxygen vacancies and the oxygen that adsorbed on the surface or the hydroxyl ion groups, respectively [53], as depicted in Figure 3c, which displays the doublet located binding energies at 159.20 and 164.80 eV correspond to the core lines of Bi-4 f5/2 and Bi-4 f7/2 , respectively, and were assigned to the Bi +3 electronic state as reported earlier [54]. There were two major peaks of C-1s spectra, as shown in Figure 3d.…”
Section: Resultsmentioning
confidence: 93%
“…Modication of band structure in a photocatalyst is fundamentally related to interruption or reduction in the recombination opportunities through the photocatalytic progression. [34][35][36][37][38][39][40] Fig. 3 shows the PL spectra of pure and co-doped BFO samples.…”
Section: Results Analysis and Discussionmentioning
confidence: 99%